Metal Nano-Oxide based Colorimetric Sensor Array for the Determination of Plant Polyphenols with Antioxidant Properties. (3rd March 2020) - Popa, Claudia Valentina; Vasilescu, Alina; Litescu, Simona Carmen; Albu, Camelia; Danet, Andrei Florin
Abstract: This work proposes a novel method for determining the composition of mixtures of natural polyphenolic compounds: caffeic acid, gallic acid, ellagic acid, rosmarinic acid and quercitrin in plants. The method is based on the formation of colored spots by these compounds upon reaction with nano-oxides of Al2 O3, ZnO, MgO, CeO2, TiO2 and MoO3 impregnated on filter paper and constituting a colorimetric sensor array (CSA). The image of the colored spots was analyzed and the intensity of the blue colour (BCI) component has shown maximum sensitivity in relation to phenolic compounds. The inverse of BCI was linearly correlated with the logarithm of the individual phenolic compound concentrations. Chemometric analysis by partial least squares regression (PLSR) of 1/BCI values for 24 synthetic mixtures of the 5 phenolic compounds measured with the colorimetric sensor array has demonstrated good correlation between the actual and the predicted concentration of quercitrin. For the other phenolic compounds, the colors measured with the colorimetric sensor array were greatly influenced by the concentrations of the other components in the mixture. The method was applied to the determination of quercitrin in medicinal teas and the results were compared to those obtained by HPLC. The discussion of the results emphasizes possible interferences in the tea samples. While further optimization of the colorimetric sensor array-based method appears necessary, tailored to the particular targeted application in real samples, the proposed method for polyphenol determination has advantages that include simplicity, low cost, and portability.